Internationalisation Of Service-Sector Small And Medium Sized Business Training And Consultancy Firms In Malaysia - Ooi, Shir May (2018)
Globalisation forces and information communication technology advancements have enabled small and medium-sized (SMEs) service firms to internationalise their business activities at an ever-increasing speed and scale. This thesis explores the internationalisation of such firms from an emerging market. In particular, it studies business training and consultancy (BTC) firms’ internationalisation decision making as well as their challenges and capabilities. The multiple-case study approach is adopted, and thirty-one in-depth interviews are conducted with members of the top management and executives from eight business training and consultation firms in Malaysia. The Uppsala model and the framework for service internationalisation are used as theoretical guidance to analyse the internationalisation of the firms. The entry modes, psychic distance, business network, internationalisation challenges, and business capabilities are analysed in this study. The result suggests that psychic distance, business network, and business capabilities, which are listed in internationalisation theories, explain the internationalisation of BTC firms from Malaysia. However, the discussion of entry modes in the framework of service internationalisation does not accurately explain the internationalisation of BTC firms from Malaysia. Language and country-of-origin perception are the major challenges for the BTC firms in this study. Business capabilities are important for BTCs to form a competitive advantage during their internationalisation. The study provides new insights into service internationalisation in SMEs from an emerging market. The application of internationalisation theories to the BTC industry in an emerging market is analysed and internationalisation challenges and capabilities are discovered. The internationalisation theories do not accurately explain the current internationalisation of the BTC firms in this study.